An identification key to the genera and species of Afrotropical Tetrigini (genera Paratettix, Leptacrydium, Hedotettix, Rectitettix nov. gen., and Alienitettix nov.gen.) with general remarks on the taxonomy of Tetrigini (Orthoptera, Tetrigidae) - Devriese, Hendrik; Nguyen, Eileen; Husemann, Martin (Zootaxa, 2023)
The Afrotropical species hitherto considered to belong to the genera Paratettix Bolivar, 1887, Leptacrydium Chopard, 1950 and Hedotettix Bolivar, 1887 are reviewed, and two new genera, Alienitettix nov. gen. and Rectitettix nov. gen., are established. Four new species are described: Alienitettix usambarensis nov. sp., Leptacrydium femurcrassum nov. sp., Leptacrydium rhombeum nov. sp. and Rectitettix burri nov. sp. Several new combinations are created: Alienitettix gilloni (Günther, 1979) nov. comb. for Paratettix gilloni, Alienitettix villiersi (Günther, 1979) nov. comb. for Paratettix villiersi, Hippodes abidjanensis (Günther, 1979) nov. comb. for Coptotettix abidjanensis, Leptacrydium nanum (Bruner, 1910) nov. comb. for Tetrix nanus and Paratettix royi (Günther, 1979) nov. comb. for Leptacrydium royi. Paratettix angustivertex Bolivar, 1908 is resurrected. It is discussed whether the North American Tetrix arenosa (Burmeister, 1838) belongs to Tetrix and Tetrigini. The following synonyms are established: Coptotettix annulipes Karsch, 1890 nov. syn. and C. convexus Hancock, 1910 nov. syn. = C. rufipes Bolivar, 1887; Paratettix asbenensis Chopard, 1950 nov. syn. = P. pallipes (Walker, 1871); Telmatettix burri Hancock, 1900 nov.syn. and Paratettix macrostenus Günther, 1979 nov. syn. = Paratettix subpustulatus (Walker, 1871); Paratettix chopardi Günther, 1979 nov. syn. = P. africanus Bolivar, 1908; Paratettix marshalli Hancock, 1908 nov. syn. = Paratettix scaber (Thunberg, 1815); Paratettix obtusipulvillus Günther, 1979 nov. syn. = Paratettix spretus Günther, 1979; and Tettix waelboecki Bolivar, 1908 nov. syn. = Leptacrydium gratiosum (Karsch, 1893). Identification keys for all species and pictures of the majority of species are presented. New country records are given. New definitions of the pronotal forms in Tetrigidae are established based on their relationship to the fore (elytra) and hind wings (alae), with a new form, the pauropronotal, being introduced for the form where the fully functional hind wings are clearly longer than the pronotum; the new form is apomorphous for the Afrotropical Tetrigini. A provisional diagnosis for the (Afrotropical) Tetrigini is given. Coptotettix Bolivar, 1887 is removed from the Tetrigini and placed near Thoradontini and Criotettigini.